2002
DOI: 10.1093/carcin/23.5.839
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid causes DNA damage in colonic cells with subsequent induction of caspases, COX-2 promoter activity and the transcription factors NF-kB and AP-1

Abstract: Evidence is accumulating that bile acids induce apoptosis in colonic cells. Therefore, it becomes important to study the underlying molecular mechanisms and the role of this phenomenon in tumor promotion. Minutes after exposure of HCT 116 and HT-29 cells to deoxycholate (DCA), DNA damage, measured using the COMET assay, was evident. Caspase-3 was rapidly activated in HCT 116 cells exposed to DCA, whereas in HT-29 cells, caspase-3 activation was delayed. Using transient transfections with reporter constructs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 38 publications
6
71
2
1
Order By: Relevance
“…At Ͼ50 M, DCA induced significant cell death, identified by visual inspection of cells and comparison of cell counts with a parallel baseline plate, fixed at the time of BA treatment. DCA is known to stimulate cell apoptosis (24). To confirm that apoptosis was not involved in the inhibitory effect of Ͻ100 M DCA on cell proliferation, cells were treated with varying doses of DCA, lysed, and probed by Western blotting for caspase-3 cleavage.…”
Section: Ba Metabolites Exert a Differential Effect On Intestinal Epimentioning
confidence: 99%
“…At Ͼ50 M, DCA induced significant cell death, identified by visual inspection of cells and comparison of cell counts with a parallel baseline plate, fixed at the time of BA treatment. DCA is known to stimulate cell apoptosis (24). To confirm that apoptosis was not involved in the inhibitory effect of Ͻ100 M DCA on cell proliferation, cells were treated with varying doses of DCA, lysed, and probed by Western blotting for caspase-3 cleavage.…”
Section: Ba Metabolites Exert a Differential Effect On Intestinal Epimentioning
confidence: 99%
“…Phosphorylation of NF-B p65 not only enhances the efficiency of DNA binding, but also provides an additional interaction site for transcriptional co-activator CBP/p300 (29). Previous studies have shown that bile acids activate NF-B signaling pathways in cancer cells (15,30). To determine whether TCA also can activate the NF-B signaling pathways, we examined the protein levels of phosphorylated IKK␣/␤ (p-IKK␣/␤) and phosphorylated NF-B p65 (p-NF-B p65).…”
Section: Tca Induces Cox-2 Expression and Chronic Inflammation Viamentioning
confidence: 99%
“…Several mechanisms have been proposed to account for enhanced cell proliferation. These include activation of protooncogenes, such as c-fos and c-jun (34), and the stimulation of cyclooxygenase-2 activity (35), with the consequent increase in prostaglandin E2 production, which is involved in inducing the resistance of malignant cells to apoptosis and enhancing their invasiveness. Our results indicated that bile acid accumulation might favor cholangiocarcinoma development by stimulation of proinflammatory mechanisms and by impairing FXR-mediated chemoprotection against genotoxic insults.…”
Section: Discussionmentioning
confidence: 99%